Cyberbullying in the name of God : critical discourse analysis of online responses to the act of de-hijabbing in Malaysia - Natrah Noor,; Bahiyah Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Islamisation phenomenon in Malaysia is characterised not only by an increased number of Islamic projects within the public institutions, but its permeation is evident in the increased awareness of hijab in the country. Since the late 1980s, hijab has attained many meanings, from a symbol of Islamic revivalism to a reconstruction of Malay identity. Today, hijab has become a normative identity of Muslim women in Malaysia. For women who have conformed to this norm, they are expected to be always wearing it and when they decide to de-hijab, the decision can trigger public opprobrium, bullying, and abuse. The de-hijabbing decision of Muslim women in Malaysia has been in the spotlight, particularly for public figures, with media representing the decision as a threat to the Muslim community and Islam in general. However, public scorn, bullying, and abuse have reached an unprecedented level and are increasingly common with the rise of public display of hijab on social media such as Instagram, Facebook, and Twitter. Using the Critical Discourse Analysis (CDA) approach and van Dijk’s (1999; 2006) Ideological Square Model, this study examines the positive self and negative other representations evident in the response of netizens to a Malaysian celebrity, Emma Maembong’s, de-hijabbing decision. The findings of this research revealed not only the discursive strategies through which an outgroup population is delegitimised in social media, but also contributed to a better understanding of the struggles faced by Muslim women in exercising their agency.